Improving Catalytic Activity in the Electrochemical Separation of CO2 Using Membrane Electrode Assemblies. Issue 1 (18th January 2022) - Schwartz, Nicholas; Harrington, Jason; Ziegler, Kirk; Cox, Philip
Abstract : The direct electrochemically driven separation of CO2 from a humidified N2, O2, and CO2 gas mixture was conducted using an asymmetric membrane electrode assembly (MEA). The MEA was fabricated using a screen-printed ionomer bound Pt cathode, an anion exchange membrane (AEM), and ionomer bound IrO2 anode. Electrocatalyst materials were physically and chemically characterized prior to inclusion within the electrode. Electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV) measurements using a rotating disk electrode (RDE) were used to quantify the catalytic activity and determine the effects of the catalyst-to-ionomer ratio. Catalysts were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) surface analysis, and (dynamic light scattering) DLS to evaluate catalyst structure, active surface area, and determine the particle size and bulk particle size distribution (PSD). The electrocatalyst layer of the electrodes were fabricated by screen printing a uniformly dispersed mixture of catalyst, dissolved anionic ionomer, and a solvent system onto an electrode supporting gas diffusion layer (GDL). Pt-IrO2 MEAs were fabricated and current-voltage relationships were determined using constant-current measurements over a range of applied current densities and flow rates. Baseline reaction kinetics for CO2 separation were established with a standard set of Pt-IrO2 MEAs.